An Archaeological Survey of Bache Peninsula, Ellesmere Island - Schledermann, Peter (ARCTIC, 1977)
During the early part of August 1977, a survey of archaeological sites was carried out in the Bache Peninsula region on the east coast of Ellesmere Island, N.W.T. with the purpose of ascertaining the feasibility of detailed prehistoric human/ecological investigations in the area in the future. . The specific objective of the Ellesmere Island Research Project was to locate sites pertaining to the various phases of Arctic prehistory, including the earliest Independence I (or Gammel Nugdlit?) sites, Independence II sites, and Dorset and Thule culture sites. The cultural associations of the various sites were generally established from a study of dwelling configurations and location in relation to present sea level, as well as fortuitous diagnostic surface finds. . The new discoveries in the Arctic Islands indicate an appreciably greater cultural continuity than previously suggested. It is perhaps more reasonable to think in terms of greater or lesser intensity of human occupation and utilization rather than extensive periods of complete abandonment of the High Arctic.